Oceanographic Fronts Shape Phaeocystis Assemblages: A High-Resolution 18S rRNA Gene Survey From the Ice-Edge to the Equator of the South Pacific - Sow, Swan L. S.; Trull, Thomas W.; Bodrossy, Levente (Frontiers in Microbiology, 2020)
The cosmopolitan haptophyte Phaeocystis is recognized as a key contributor to marine biogeochemical cycling and important primary producer within polar marine environments. Yet, little is known about its solitary, non-colonial cell stages or its distribution during the colder, low-productivity seasons. We examined the biogeography of Phaeocystis along a high-resolution (0.5-degree latitudinal interval) transect from the Antarctic ice-edge to the equator of the South Pacific, in austral autumn-winter. Using high-throughput 18S rRNA gene sequences with single nucleotide variable (zero-radius) operational taxonomic units (zOTU) allowed us to explore the possibility of strain-level variation. From water samples within the upper water column, we show the presence of an abundant Phaeocystis assemblage that persisted during the colder months, contributing up to 9% of the microbial eukaryote community at high latitudes. The biogeography of Phaeocystis was strongly shaped by oceanographic boundaries, most prominently the Polar and Subantarctic Fronts. Marked changes in dominant P. antarctica zOTUs between different frontal zones support the concept that ecotypes may exist within the Phaeocystis assemblage. Our findings also show that the Phaeocystis assemblage did not abide by the classical latitudinal diversity gradient of increasing richness from the poles to the tropics; richness peaked at 30°S and declined to a minimum at 5°S. Another surprise was that P. globosa and P. cordata, previously thought to be restricted to the northern hemisphere, were detected at moderate abundances within the Southern Ocean. Our results emphasize the importance of oceanographic processes in shaping the biogeography of Phaeocystis and highlights the importance of genomics-based exploration of Phaeocystis, which have found the assemblage to be more complex than previously understood. The high winter relative abundance of the Phaeocystis assemblage suggests it could be involved in more complex ecological interactions during the less productive seasons and should be considered for future studies to better understand the ecological role and strategies of this keystone species.